Forces of Nature New Perspectives on Korean Environments - Fedman, David; Kim, Eleana J.; Park, Albert L. (Cornell University Press, 2023)
Bringing together a multidisciplinary conversation about the entanglement of nature and society in the Korean peninsula, Forces of Nature aims to define and develop the field of the Korean environmental humanities. At its core, the volume works to foreground non-human agents that have long been marginalized in Korean studies, placing flora, fauna, mineral deposits, and climatic conditions that have hitherto been confined to footnotes front and center. In the process, the authors blaze new trails through Korea's social and physical landscapes. What emerges is a deeper appreciation of the environmental conflicts that have animated life in Korea. The authors show how natural processes have continually shaped the course of events on the peninsula-how floods, droughts, famines, fires, and pests have inexorably impinged on human affairs-and how different forces have been mobilized by the state to variously, control, extract, modernize, and showcase the Korean landscape. Forces of Nature suggestively reveals Korea's physical landscape to be not so much a passive context to Korea's history, but an active agent in its transformation and reinvention across centuries.